The Rhythm of Sense (Itinera, 2024)
The task that awaits those who have noticed the devastation of the truth prevailing today lies in coming to terms with the illusory nature of the political proposals that European leaders formulated during the 20th century and which, despite their diversity, are based on a single interpretation of the sense of Being in terms of “nihilism”. Now, we do acknowledge that ample space has been reserved in the last fifty years to show the criminal nature of the fascist and Nazi projects, as well as the alienation that emblematically characterizes the liberal model, particularly in its American version. That is why it now proves extremely urgent to clarify the spiritual presuppositions that favored the disastrous advent of Bolshevism in the Soviet Union. Here is what E.E. Cummings set out to do during a trip made in the 1930s to Stalin’s Russia and whose ripest fruits the American poet collected in a very precious diary emblematically entitled Eimi (I am). Awakening a sense of Being thus becomes the escape route Cummings devised to bring Western man back into that dimension capable of renewing in each of us that need for rootedness, which guarantees the possibility of an authentic existence.